Life cycle comparison of carpet dyeing processes. Issue 1 (28th March 2019) - Ponder, Celia; Gregory, Bill; Griffing, Evan; Li, Yong; Overcash, Michael
Abstract : Carpet manufacturing continues to adopt advanced technologies and new processes. One important process is central to the carpet product, dyeing for the color and beauty of patterns derived for modern carpets. Carpets and fibers are dyed by a variety of different processes at different stages of production, from the fiber, the yarn, or the carpet, depending on the product use, economy of the process, and market demand for the color. Dyeing technology for carpets has evolved to advanced processes and is discussed in this paper. Fiber can be dyed as it is extruded, as in the case of solution dyeing; yarn can be dyed as in skein, or space dyeing; or whole carpet pieces can be dyed as in beck or continuous dyeing. This paper is the first direct comparison of these five carpet dyeing processes with the goal to understand the technology changes to more advanced manufacturing. Using a life cycle approach, gate‐to‐gate (within the factory) inventories are created to assess resource and energy consumption associated with each of the processes. The life cycle inventories are created based on process flow models of product manufacturing to provide transparency. A single color agent (beta‐copper phthalocyanine) and a single face fiber (nylon 6) are used for the comparison. The older batch processes, such as beck and skein, consume the most water and energy, while the most recent advanced process of solution dyeing uses the least amount of energy and water.